Derangement of Serum Electrolytes in Term Infants with Perinatal Asphyxia Presenting to NICU of Bacha Khan Medical Complex Swabi - Hussain, Tariq; Sijad Ur Rehman; Afridi, Haji Gul; Inayat Ullah; Hussain, Saddam; Muhammad Haris (Indus Journal of Bioscience Research, 2024)
The Perinatal asphyxia remnants the critical condition connected with the important morbidity and mortality in the infants, particularly in the resource-limited settings. So, this cross-sectional study aimed to consider prevalence of the serum electrolyte confusions in the term infants diagnosed with the perinatal asphyxia acknowledged to Neonatal Intensive Care Unit the (NICU) at Bacha Khan Medical Complex Swabi. The total of 100 term infants with an Apgar score of less than 7 at 5 minutes or the demanding resuscitation at the birth was included. The Electrolyte levels were measured for the sodium, potassium, calcium, and the chloride, and derangements were identified based on the established reference ranges. The Results indicated that 51% of the infants experienced hyponatremia, although 36% had hypokalemia and 35% hypocalcemia. The Statistically significant associations were found between the electrolyte abnormalities and the poorer clinical outcomes, with the infants exhibiting derangements requiring longer the NICU stays (mean 12.5 ± 4.6 days vs. 7.2 ± 3.1 days) and the higher incidence of the ventilatory support needs (35% vs. 10%). So these findings underscore critical importance of early recognition and the management of the electrolyte imbalances in the asphyxiated infants to improve the clinical outcomes and optimize neonatal care practices. For Further research is warranted to explore long-term implications of these disturbances and develop standardized management protocols in the NICUs.